MODEL PEMBELAJARAN CONCEPT ATTAINMENT DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Dini Palupi Putri (Jurnal Tatsqif, 2017)
This study originated from the lack of student mastery of the math concepts and math materials often mistakenly understood by students. The purpose of this study was to determine how far an increase understanding of Mathematics Concepts fifth grade students of SD Negeri 05 South Curup after applied learning model Concept Attainment. This type of research is a classroom action research that consisted of 3 cycles, each cycle consisting of four stages namely planning, action, observation and reflection. The technique of collecting data through observation and evaluation tests. Data analysis techniques through test data pengelolahan classical completeness learning outcomes, pengelolahan learning outcomes data, and test data processing observation. The results of observations of the activities of teachers and students has increased from cycle to cycle, namely from the category enough in the first cycle, the category enough in the second cycle, and both categories at the third cycle. The results of the study test understanding of the concept in the first cycle, the second cycle and the third cycle in a row shows the classical learning completeness students 61.11%, 70.08% and 83.04%. Improved results of tests and observation sheet understanding of the concept of the first cycle to the third cycle, it can be concluded that the application of the Conce pt Attainment can improve the understanding of mathematical concepts fifth grade students in mathematics.